Recovery stress effect of crimped NiTi SMA fibers on dynamic direct tensile behavior of mortar with considering fiber volume fraction. (1st July 2022) - Choi, Eunsoo; Choi, Jongkwon; Seo, Junwon
Abstract: The effect of fiber content and the recovery stress of SMA crimped fiber on the dynamic direct tensile resistances of reinforced mortar were investigated in this study through experimental tests with middle strain rates. Thus, this study considered two volume fractions of fibers, namely, 1.0% and 1.5%. For the static test, the tensile resistances of the reinforced mortar increased with more added fiber content, whereas the recovery stress increased the post-cracking strength and reduced the strain capacity. For the dynamic tensile test, the post-cracking strength and softening fracture energy of the 1.5% fiber content specimens were lower than those of the 1.0% fiber content specimens. However, the strain capacity and peak toughness of the 1.5% fiber content specimens were higher than those of the 1.0% fiber content specimens. The reduction of peak strength in the dynamic case is attributed to the sensitivity of the reinforced mortar and the greater homogeneity of the 1.5% fiber content specimens. The recovery stress also increased the dynamic post-cracking strength and reduced the strain capacity, and it had a greater effect for 1.0% fiber content specimens. Generally, all tensile resistance parameters were sensitive to the strain rate, and the rate sensitivity was more significant for the 1.5% fiber content specimens. It seems that adding 1.0% fiber content into mortar is more effective than adding 1.5% fiber content on the dynamic tensile resistances of reinforced mortar, with higher post-cracking strength and the higher effect of recovery stress.